2019
DOI: 10.3310/hta23390
|View full text |Cite
|
Sign up to set email alerts
|

Three wound-dressing strategies to reduce surgical site infection after abdominal surgery: the Bluebelle feasibility study and pilot RCT

Abstract: Background Surgical site infection (SSI) affects up to 20% of people with a primary closed wound after surgery. Wound dressings may reduce SSI. Objective To assess the feasibility of a multicentre randomised controlled trial (RCT) to evaluate the effectiveness and cost-effectiveness of dressing types or no dressing to reduce SSI in primary surgical wounds. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 90 publications
0
48
0
Order By: Relevance
“…In a main trial, it is expected that training for recruitment and materials used to optimise recruitment will be available based on lessons learnt in this pilot. It is likely that a main two-group trial would address whether ‘no dressings’ are non-inferior to a simple dressing in terms of SSI; this is the comparison is of greatest value to the National Health Service 18. A main trial with three groups would be more efficient than a separate trial to test the superiority of ‘glue-as-a-dressing’ to simple dressings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a main trial, it is expected that training for recruitment and materials used to optimise recruitment will be available based on lessons learnt in this pilot. It is likely that a main two-group trial would address whether ‘no dressings’ are non-inferior to a simple dressing in terms of SSI; this is the comparison is of greatest value to the National Health Service 18. A main trial with three groups would be more efficient than a separate trial to test the superiority of ‘glue-as-a-dressing’ to simple dressings.…”
Section: Discussionmentioning
confidence: 99%
“…Skin transfers (temporary adherent tattoos) were placed next to the wound to encourage adherence to allocated dressing type after leaving the operating theatre (figure 1). The feasibility of collecting other data (likely to be used in a main trial) and their completeness was investigated for: patient and observer reported questionnaires measuring SSI with the newly validated WHQ; patient and observer reported questionnaires to assess symptoms and experiences of wounds and dressings; preference-based health-related quality of life (EuroQoL-five-dimension-five-level: EQ-5D-5L) 17; wound complications and resource use 18. A face-to-face wound assessment was carried out at 4-6 weeks to validate the WHQ 19.…”
Section: Methodsmentioning
confidence: 99%
“…After title and abstract screening by two reviewers (RM and JP), further 4584 articles were removed, resulting in 26 articles for full‐text review. Following full‐text review, further 18 articles were excluded and 8 articles 36‐43 included in review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarises the eight included studies. Of them, five were conducted in the United States, 36,37,41‐43 and three in the United Kingdom 38‐40 . All studies were published between 2013 and 2019.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation